2001
DOI: 10.1046/j.1471-4159.2001.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Aβ peptides increase oxidative stress in vivo through NMDA‐receptor and nitric‐oxide‐synthase mechanisms, and inhibit complex IV activity and induce a mitochondrial permeability transition in vitro

Abstract: Beta amyloid (Ab) peptides accumulate in Alzheimer's disease and are neurotoxic possibly through the production of oxygen free radicals. Using brain microdialysis we characterized the ability of Ab to increase oxygen radical production in vivo. The 1±40 Ab fragment increased 2,3-dehydroxybenzoic acid ef¯ux more than the 1±28 fragment, in a manner dependent on nitric oxide synthase and NMDA receptor channels. We then examined the effects of Ab peptides on mitochondrial function in vitro. Induction of the mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(110 citation statements)
references
References 39 publications
5
103
1
1
Order By: Relevance
“…Several other neurotoxic mechanisms, such as the formation of ionic channels that allows increased calcium uptake by mitochondria and mtPTP opening with subsequent inhibition of respiratory complexes [25], have been proposed for Aβ -induced neurotoxicity that is mediated through intramitochondrial interactions. The fact that Aβ can accumulate both intracellularly and intramitochondrially has been demonstrated by Rosales-Corral et al (2012) [26], in which intracerebral injection of fibrillar Aβ caused accumulation of Aβ both intracellularly and intramitochondrially, deep within the cristae, thereby supporting other investigators' views of intramitochondrial accumulation of Aβ. In addition to inhibiting mitochondrial respiratory complex activities in AD patients, disturbances in mitochondrial dynamics have also been demonstrated.…”
Section: Amyloid β Peptide and Mitochondrial Interaction As Triggerinsupporting
confidence: 58%
See 1 more Smart Citation
“…Several other neurotoxic mechanisms, such as the formation of ionic channels that allows increased calcium uptake by mitochondria and mtPTP opening with subsequent inhibition of respiratory complexes [25], have been proposed for Aβ -induced neurotoxicity that is mediated through intramitochondrial interactions. The fact that Aβ can accumulate both intracellularly and intramitochondrially has been demonstrated by Rosales-Corral et al (2012) [26], in which intracerebral injection of fibrillar Aβ caused accumulation of Aβ both intracellularly and intramitochondrially, deep within the cristae, thereby supporting other investigators' views of intramitochondrial accumulation of Aβ. In addition to inhibiting mitochondrial respiratory complex activities in AD patients, disturbances in mitochondrial dynamics have also been demonstrated.…”
Section: Amyloid β Peptide and Mitochondrial Interaction As Triggerinsupporting
confidence: 58%
“…This includes disturbances in mitochondrial structure, impairment of dynamin -related peptide (Drp1) and imbalances in fission and fusion, with consequent neuronal damage and synaptic loss [27]. Significant disturbances of mitochondrial proteins and lipids also occur following intramitochondrial accumulation of Aβ, which in turn causes functional impairment of mitochondria in AD [26].…”
Section: Amyloid β Peptide and Mitochondrial Interaction As Triggerinmentioning
confidence: 99%
“…Alzheimer's disease is a neurodegenerative disorder characterized by the presence in the brain of senile plaques, containing an amyloid core made of ␤-amyloid peptide (␤A). ␤A is a neurotoxic polypeptide of 39-43 aa that can induce mPTP opening in isolated brain mitochondria (15)(16)(17). Previously, we have shown that addition of ␤A promotes fluctuations of intracellular Ca 2ϩ concentration, and Ca 2ϩ -and CsA-dependent fast, transient mitochondrial depolarizations in astrocytes, indicating activation of PT (18,19).…”
Section: Pt-dependent Cell Death and Polyp Ppx Expression Protects Amentioning
confidence: 97%
“…Canevari et al, and Casley et al, showed that nonsynaptic brain mitochondria from rats treated with a truncated form of Aβ displayed a specifically complex IV inhibition, whereas other RC complexes remained unaltered (Canevari et al, 1999;Casley et al, 2002). Moreover, Parks et al, reported Aβ-induced complex IV inhibition in rat liver isolated mitochondria (Parks et al, 2001). This complex IV inhibition could lead to further instability or alterations in the assembly of this complex or the respirasome, subsequent alterations in the electron flux, and even increased ROS production due to the backup of reduced complexes upstream in the RC, as mentioned in previous sections.…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%